Community Empowerment in Stunting Prevention: Implementation of the UBaMa Method (Ultra Violet Rays and Baby Massage) - Tinuk Esti Handayani; Teta Puji Rahayu (Knowledge Dynamics, 2024)
Babies are an age group that is vulnerable to stunting. The incidence of stunting in Ngariboyo District in 2022 was 185 (13.14%) children under five, the highest occurred in Mojopurno Village, which was 49 (19.91%) children under five. The purpose of this activity is to improve the understanding, attitude and behavior of baby mothers in stimulation with the UBaMa method. The method carried out is to conduct a pre-test for baby mothers, followed by providing explanations and training on the UBaMa method. After that, the baby's mother was asked to carry out UBaMa at home, evaluated at the second meeting and so on until the fourth meeting. After the fourth meeting, a post-test was carried out. The results achieved were an improvement in the skills of mothers under five to do stimulation with the UBaMa Method with a proficiency of 68%. Knowledge Improvement with pre-test 49 and post-test 83.75. The UBaMa Stimulation Method (Ultra Violet and Baby Massage) can improve the growth and development of babies. It is recommended that the baby's mother periodically stimulate UBaMa at least 3 times a week to increase breast milk production so that it can be used to prevent stunting.